Budowa portfeli rynkowych i ocena efektywności inwestycji z wykorzystaniem rozkładów stabilnych - Krężołek, Dominik (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this paper is to present some properties of stable distributions and its implementation in portfolio management. Two strategies are presented: the first one is to minimize the coefficient of variation of the portfolio's return and the second one is to minimize the coefficient of variation subject to the assumption that the expected portfolio's return coincides with the location parameter of the stable distribution. Afterwards these strategies are compared using Sharpe and Treynor indexes of efficiency. The results show that the second strategy reflects the real behaviour of asset returns (including heavy-tailed property of financial data) better than the first one. The application of these strategies in solving of portfolio selection problems in the Polish capital market is given. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 185-192